THE EFFECT OF FUEL INJECTION TIMING ON PERFORMANCE AND EXHAUST EMISSIONS IN DIESEL MOTORS WITH MIXED DIESEL FUEL AND POME BIOGAS - Sulisthirafi, Arkanzach
One of the innovations of motor fuel technology is the use of two types of fuel in an internal combustion engine or so-called dual fuel engine. One of the goals of this innovation is to reduce emissions of carbon monoxide (CO), hydrocarbons (HC), nitrogen oxide (NOx), sulfur oxide (SOx) and soot. Two types of fuel used in this type of motor fuel are diesel and biogas POME. Based on these problems, the objectives of this research are: 1) Knowing the effect of changes in fuel injection time on performance and exhaust gas emissions of diesel motors with diesel fuel and POME biogas, 2) Determining the optimum fuel injection time of diesel and POME biogas for simulation results on a diesel engine. The method used in this study is a quantitative simulation using AVL Boost software, with the limitation of using the Yanmar Diesel Fuel Motor type TF 155 R-DI, as a dual fuel diesel engine. Based on the results and analysis on the simulation, it can be concluded that: 1) The effect of fuel injection on performance and emissions appears to occur with changes in fuel injection that are increasingly advanced in dual fuel diesel motors. Advances in fuel injection led to a fluctiative data in torque, power, BMEP, volumetric efficiency and an increase in specific fuel consumption. NOx production increases along with progress in fuel injection timing until 10o before TDC, then the result of NOx decreases. The results of soot emission tend to decrease with changes in fuel injection that are increasingly advanced, 2) Progress when fuel injection is 10o before the top dead center of the piston on a dual fuel diesel motor produces the most optimum performance and emission data.